Work-Related Stress, Adversity Quotient, and Psychological Well-Being of Local College Instructors in the New Normal - Bawar, Joanna Belle; Yango, Antonio; Bermudo, Pedrito Jose (Technium Social Sciences Journal, 2023)
In the past two years, teachers’ role has become more complex and diverse due to continuous change in curriculum and educational reforms, updating of teaching methodology, adapting, and incorporating use of technology, and increased of social aggressiveness (Gurrea, 2021). The aim of this study was to determine the work-related stress and adversity quotient as predictor of psychological well- being of local college instructors in the new normal. Specifically, it investigated the respondents’ level of work-related stress, adversity quotient in terms of control, ownership, reach and endurance, level of psychological well-being in terms of autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance. Further, the study probed the relationship between the respondents’ level of work-related stress and adversity quotient, level of work-related stress and well-being, and adversity quotient and level of psychological well-being. Finally, it probed the predictive ability of the level of work-related stress, and adversity quotient, taken singly or in combination, of level of psychological well-being of the local college instructors in the new normal. The findings revealed that there was a significant low negative relationship between work-related stress and adversity quotient in terms of ownership . Likewise, no significant relationship was noted between adversity quotient and psychological well-being. Lastly, the work-related stress and adversity quotient did not significantly predict the respondents’ level of psychological well-being. It was concluded in the study that an increase in work-related stress would reduce capability of college instructors to develop interpersonal relationships and have difficulty showing empathy with others; perceived adversity does not affect their psychological well-being; and work-related stress and adversity quotient do not predict psychological well-being of.